Impacts and benefits of retail audit to maximize market share, product availability and visibility of MGI products in Dhaka wing - Munshi, Md. Rubel (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.